Weekday-Weekend Sedentary Behavior and Recreational Screen Time Patterns in Families with Preschoolers, Schoolchildren, and Adolescents: Cross-Sectional Three Cohort Study - Sigmundová, Dagmar; Sigmund, Erik (International journal of environmental research and public health, 2021)
BACKGROUND: Excessive recreational screen time (RST) has been associated with negative health consequences already being apparent in preschoolers. Therefore, the aim of this study was to reveal parent-child sedentary behavior, and RST patterns and associations with respect to the gender, age category of children, and days of the week. METHODS: Our cross-sectional survey included 1175 parent-child dyads with proxy-reported RST data collected during a regular school week during the spring and fall between 2013 and 2019. The parent-child RST (age and RST) relationship was quantified using Pearson's (rP) correlation coefficient. RESULTS: Weekends were characterized by longer RST for all family members (daughters/sons: +34/+33 min/day, mothers/fathers: +43/+14 min/day) and closer parent-child RST associations than on weekdays. The increasing age of children was positively associated with an increase in RST on weekdays (+6.4/+7.2 min per year of age of the daughter/son) and weekends (+5.8/+7.5 min per year of age of the daughter/son). CONCLUSIONS: Weekends provide a suitable target for implementation of programs aimed at reducing excessive RST involving not only children, but preferably parent-child dyads.
Keywords: Cross-Sectional Studies; weekdays; sedavý životní styl; daughter; cvičení; Sedentary Behavior; mladiství; Cohort Studies; son; Television; mužské pohlaví; průřezové studie; father; čas strávený před obrazovkou; preschoolers; kohortové studie; dítě; Child; televize; ženské pohlaví; screen time; Humans; weekends; Screen Time; Exercise; Female; mother; Adolescent; lidé; Male